2012
DOI: 10.1007/s12663-012-0418-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of PRP in the Reconstruction of Mandibular Segmental Defects Using Iliac Bone Grafts

Abstract: This retrospective study was conducted to evaluate the role of platelet-rich plasma (PRP) in the reconstruction of segmental mandibular defects using iliac bone grafts. Thirteen patients underwent reconstruction of post-resection segmental defects of the mandible using titanium reconstruction plates, cortico cancellous iliac bone graft. The patients were randomly separated into two groups. One group of the patients received a PRP graft in addition to the iliac bone graft. Post-operative dimensions of the graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…PRP has been reported to stimulate bone regeneration [ 5 - 8 ]. Recently, second-generation platelet concentrates such as platelet-rich fibrin and concentrated growth factor have been noted to slowly release platelet growth factor and enable healing of bony defect in vivo [ 19 - 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRP has been reported to stimulate bone regeneration [ 5 - 8 ]. Recently, second-generation platelet concentrates such as platelet-rich fibrin and concentrated growth factor have been noted to slowly release platelet growth factor and enable healing of bony defect in vivo [ 19 - 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ [33][34][35][36][37] On the other hand, other studies in the review got comparable or even better result despite not utilizing PRP. [23,26] Therefore it may be difficult to ascribe the outcome to any beneficial effect of PRP as claimed by the authors.…”
Section: Ameloblastic Fibromamentioning
confidence: 88%
“…Some authors such as Marx et al, Magesh et al [ 18 ], and Aimetti et al [ 19 ] evaluated the effect of PRP on bone regeneration in human. In their studies, the bone defects were treated with an autogenous bone graft alone or in combination with PRP, and they all demonstrated that the use of PRP along with an autogenous bone graft were advantageous since it enhanced the quantity of newly formed bone.…”
Section: Discussionmentioning
confidence: 99%